Editorial - Verma, Ravinder (Indian Farming, 2021)
Farmers or the ‘Annadata’ of our country are the backbone of the economy. They are the ones who work diligently throughout the year to ensure that there is enough food for everyone. Farmers are a living repository of traditional knowledge owing to their vast farm experience. Despite having a ‘Know How’, the knowledge and innovations the farmers have not been valued much and they have been a mere participant and not as a partner in the scientific research. The wisdom available with the farmers have not been channelized enough to evaluate suitable options for different production systems. On the other hand, the scientific technology from the lab has not been effectively transmitted in the farmer’s field. However, to some extent, the increasing advancement in technology has resulted in increasing the agricultural production.Though farmers are the one who provide our basic food, they suffer the most with the prevailing high inflation in agricultural inputs, pressure on land and water resources. Keeping these challenges in mind, ICAR launched the Farmer FIRST Programme (FFP) to improve the livelihood of the farmers and double their income by 2022. FFP has spread across the country and the interaction between farmers and scientists is taking place in real-time. The objective of our Hon’ble Prime Minister to double the income of farmers by 2022 is seemingly possible according to the success stories recorded in many FFPs centre that are presented in this special issue on the Farmer’s Day. The FFP has been able to penetrate into the villages and they have joined to adopt the technical interventions. This is gradually bringing the spillover effects across the country. The objective of farmers-scientists interface in farmer’s farm is successfully taking place in all the FFPs centres. This is expected to bring changes in technological interventions that are in accordance with the needs of farmers and bring farmers closer to scientific knowledge.We are happy to share the contribution made by FFP in this special issue on the occassion of National Farmer’ Day or Kisan Diwas.